Effect of gamma irradiation on shelf life and quality of Broiler meat (SAARC Journal of Agriculture, 2019)
The experiment was conducted on fresh broiler meat treated with 60Co gamma irradiation having dose of 0 (T0), 1 (T1), 2 (T2) and 3.5 kGy (T3)) and stored 0, 30 and 60 days at -20ºC to estimate the effect on proximate, sensory, physicochemical, biochemical and microbial changes in broiler meat. Factorial experiment (4x3) in completely randomized design (CRD) replicated three times per cell was applied to study the variation among treatment combination. Color was changed significantly (p